The Duality of Clowns in W. B. Yeats’s “The Mask”– Who is the ‘I’? - Lala A. Mahmood; Larin J. Kharib; Sara S. Hamatofiq; Kauthar F. Jamal; Shajwan N. Fatah (Polish Journal of English Studies)
This article offers a close reading of William Butler Yeats’s “The Mask” (1910), a poem that has generated diverse critical interpretations, particularly concerning themes of gender and theatricality. Critics have read the poem through a biographical lens – often situating it within the personal life and romantic experiences of the poet himself. Unlike such interpretations, this study shifts the focus to the poem’s rhetoric, visual imagery, and the layered symbolism of the “mask.” By following semiotic reading (Ferdinand de Saussure), the analysis decodes the language, decenters the most literal meanings, and examines the figure of the clown through evocative phrases such as “burning gold” and “emerald eyes”. In this study, we aim to interpret the clown not merely as a performative or external figure, but also as a metaphor for the fragmented and conflicted inner self – an identity concealed beneath layers of artifice and aesthetic expression. Drawing on the French psychoanalyst Jacques Lacan’s theory of otherness, the essay interprets the clown’s identity through the dynamics of the big Other and the small other, demonstrating how these forces simultaneously shape and destabilize the ‘I’. It explores the conflict between the inner voice behind the mask and the power imposed by social norms. Ultimately, the essay proposes a philosophically informed reading of Yeats’s poem, one that foregrounds its rhetorical texture and symbolic depth rather than limiting its interpretation to personal biography. This act highlights the enduring richness of Yeats’s poetic vision and its capacity to engage with the profound questions of selfhood, perception, and representation.